ALGORITMA NEWTON RAPHSON DENGAN FUNGSI NON-LINIER - Santiyasa, I Wayan (Jurnal Ilmu Komputer; Vol. 2, No. 1 April 2009)
Studies on the characteristics of non-linear function can be either experimental ortheoretical. One part of the theoretical analysis is to perform computation. For thispurpose computation, numerical methods can be used in the complete equations of thecomplex, such as non-linear equation. There are a number of numerical methods thatcan be used to complete the non-linear equation, is the Newton-Raphson method.
Keywords: Numeric, Newton Raphson